Math, asked by sudhanshukmr57, 6 months ago

koi mera help krega ??
and please don't put wrong answer​

Attachments:

Answers

Answered by bk060734
1

Step-by-step explanation:

i think it will be the ansr

Attachments:
Answered by senboni123456
1

Step-by-step explanation:

We have,

 {2}^{2x}  - 3 \times  {2}^{x + 2}  + 32 = 0

 \implies ({2}^{x} )^{2}  - 12. {2}^{x}  + 32 = 0

let \:  \:  {2}^{x}  = y

Then, we have,

 {y}^{2}  - 12y + 32 = 0

 \implies {y}^{2}  - 4y - 8y + 32 = 0

 \implies(y - 4)(y - 8) = 0

 \implies \: y = 4 \:  \: or \:  \: y = 8

 \implies {2}^{x}  = 4 \:  \: or \:  \:  {2}^{x}  = 8

 \implies \: x = 2 \:  \: or \:  \: x  = 3

Similar questions